An anthology of contemporary Bengali plays by Bratya Basu - Basu, Brātya author
"This anthology of six selected plays, written between 2000 and 2020 by Bratya Basu, winner of the Sahitya Akademi Award 2021, is the first collection of Bengali plays that blends avant-garde, pop and traditional cultures with contemporary dramatic themes. The six plays, freshly translated into English, each bring a uniquely Bengali and Indian perspective to the intermingling of past and present, global and local, and magical and real in a postmodern pastiche about India today. The collection is divided into three thematic sections: 1) 'Poignant Challenges, Soulful Remorse' examines power in Indian politics, religion, and family; 2) '(In)visible Boundaries, (Un)democratic Choices' explores the relationship among democracy, nation building, and the role of women in intergenerational political struggle; [and] 3) 'Intimately Political, Politically Intimate' navigates queer identity, mental health and the fabulation of modern Bengali life in a 21st-century India straddling the progressive politics that removed section 377 and Hindu nationalisms that stoke new conservatisms" -- Provided by publisher.